SURFACE PLASMON RESONANCE (SPR) CURVATURE PHENOMENON USING OTTO CONFIGURATION AS SATURATED AND UNSATURATED FATTY DETECTION ON CHOLESTEROL FOOD - Fatimah Nopriardy; Lufsyi Mahmudin; Kamsul Abraha; Edi Suharyadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Surface Plasmon Resonance (SPR) on thin layer of conductive 50:1 PVA-coated silver nanoparticles ( AgNPs@PVA ) 0.02 M on 11-20 nm using Otto Configuration have been observed for monitoring cholesterol level of crude palm oil time-cooking for food-cholesterol. Its has been proved gap between prism/air/silver on 850 nm. Surface Plasmon Resonance (SPR) phenomenon analyzed by HeNe laser on ( = 632,8 nm ). SPR curvature has been showed by observing reflectance of laser incident angle variation on the prism. SPR angle for the prism/Ag system is (44.4 ± 0.05)° with the reflectance value on 0.8. Due to the addition of AgNPs@PVA ,also after the reaction for one-time cooking of with quail eggs ( high-cholesterol/high-unsaturated fatty ), SPR angle shifts to (47,8 ± 0.05)° with the reflectance value on 0.58 using MATLAB simulation. The shifting on SPR angle shows that the sensitivity SPR is a biosensor. Keywords : surface plasmon resonance (SPR), Otto configuration, cholesterol food.